On the Nexus between Economic growth and Environmental Degradation in 28 Countries Classified by Income Level: A Panel Data with an Error-components Model - Ruiz-Alemán, Mijail Eduardo; Carbajal-De-Nova, Carolina; Venegas-Martínez, Francisco (International Journal of Energy Economics and Policy, 2023)
This paper aims to examine the relationship between economic growth and environmental degradation in a sample of 28 countries. A panel data model is used dividing the sample into four groups classified by income level where fixed and random individual effects are estimated without the time component using an error-components model (ECM). Annual data from the World Bank for carbon dioxide emissions per capita and gross domestic product per capita are used for the period 1970-2016. The empirical results and their graphical analysis, using a panel data approach with an ECM, suggest an absence of an Environmental Kuznets Curve (EKC) in the whole sample. These results considering panel data with an ECM, 28 countries and 46 years differ from many of the studies that support the existence of an EKC in similar samples.